Ma’had Al-Zaytun Artikulasi Ke-Islaman Dan Ke-Indonesiaan Di Pendidikan Pesantren - taufik nugroho (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2020)
The research aims to reveal Ma’had Al-Zaytun as an Islamic educational institution in the aspects of ideology, direction and goals of education. The importance of this research is because a growing issue in society says that Ma’had Al-Zaytun carries a hidden agenda of "building the Islamic State of Indonesia in the long term". This study uses a qualitative approach with data collection methods: observation, participation and interviews. The results of this study are as follows: there has been a change in the social basis during the years 1970-1990. The change in the social basis is a change in the generation of the senior Indonesian Islamic State bearers with the pressure of the struggle for structural Islamic ideology to the new generation which emphasizes on the inclusive substantive Islamic struggle. The choice of the new generation's model of struggle is Ma’had Al-Zaytun. This is an articulation of Islam and Indonesiannes that makes Islam a spreader of peace, not a spreader of threats.